2019
DOI: 10.21091/mppa.2019.1002
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Training Load in Dance: The Construct Validity of Session-RPE

Abstract: OBJECTIVE: The session rating of perceived exertion (session-RPE) is a practical and non-invasive method that allows a quantification of internal training load (ITL) in individual and team sports. As yet, no study has investigated its construct validity in dance. This study examines the convergent validity between the session-RPE method and an objective heart rate (HR)-based method of quantifying the similar ITL in vocational dance students during professional dance training. METHODS: Ten dance students (4 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 27 publications
2
15
2
Order By: Relevance
“…Even though all correlation coefficients were lower than stated by Chen et al (2002) [10] and only medium correlations could be observed, the subgroup analysis in the field of J/MD showed a correlation that was only slightly lower. Thus, these results are also somewhat lower than those of Surgenor et al (2019) [24], who found high construct validity for RPEs. Based on the WHO (2010) [25] health recommendations for physical activity, which are 150 min per week of moderate intensity (corresponds to a 5 or 6 on a scale of 0-10) or alternatively 75 min per week of strenuous intensity (corresponds to a 7 or 8 on a scale of 0-10) for people between 18 and 64 years of age, the dance teachers' teaching workload is significantly higher.…”
Section: Rpe To Assess Physical Work Loadscontrasting
confidence: 72%
“…Even though all correlation coefficients were lower than stated by Chen et al (2002) [10] and only medium correlations could be observed, the subgroup analysis in the field of J/MD showed a correlation that was only slightly lower. Thus, these results are also somewhat lower than those of Surgenor et al (2019) [24], who found high construct validity for RPEs. Based on the WHO (2010) [25] health recommendations for physical activity, which are 150 min per week of moderate intensity (corresponds to a 5 or 6 on a scale of 0-10) or alternatively 75 min per week of strenuous intensity (corresponds to a 7 or 8 on a scale of 0-10) for people between 18 and 64 years of age, the dance teachers' teaching workload is significantly higher.…”
Section: Rpe To Assess Physical Work Loadscontrasting
confidence: 72%
“…Consistent with both Jeffries et al (2016) and Surgenor and Wyon (2019), we report weaker relationships between s-RPE and objective measures in ballet class compared with rehearsals. While each of these studies attributed this finding to the difference in dance genre (i.e., ballet class vs contemporary rehearsals), and ballet not being the participants' primary discipline, neither of these explanations explain the current results.…”
Section: Discussionsupporting
confidence: 83%
“…Both the rmcorr and individual correlations observed between s-RPE and objective measures in the present study are slightly larger than both group (r = 0.71; Surgenor and Wyon, 2019) and individual (r = 0.72 ± 0.13; Jeffries et al, 2016) correlation coefficients reported in pre-professional contemporary dancers. Classical ballet and contemporary dance differ in their frequency of jumps (4.99 ± 4.93 vs. 1.71 ± 2.21 jumps per min), lifts (0.97 ± 2.53 vs. 0.12 ± 0.23 lifts per min), and changes of direction (3.34 ± 1.89 vs. 0.58 ± 0.58 changes of direction per min; Wyon et al, 2011).…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations